Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 10 - Quadratic Equations - 10.3 - Quadratic Formula - Problem Set 10.3 - Page 453: 29


{$\frac{-5 - \sqrt {73}}{4},\frac{-5+\sqrt {73}}{4}$}

Work Step by Step

Step 1: Comparing $2x^{2}+5x-6=0$ to the standard form of a quadratic equation, $ax^{2}+bx+c=0$, we find: $a=2$, $b=5$ and $c=-6$ Step 2: The quadratic formula is: $x=\frac{-b \pm \sqrt {b^{2}-4ac}}{2a}$ Step 3: Substituting the values of a, b, and c in the formula: $x=\frac{-(5) \pm \sqrt {(5)^{2}-4(2)(-6)}}{2(2)}$ Step 4: $x=\frac{-5 \pm \sqrt {25+48}}{4}$ Step 5: $x=\frac{-5 \pm \sqrt {73}}{4}$ Step 6: $x=\frac{-5 - \sqrt {73}}{4}$ or $x=\frac{-5 + \sqrt {73}}{4}$ Step 7: Therefore, the solution set is {$\frac{-5 - \sqrt {73}}{4},\frac{-5+\sqrt {73}}{4}$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.